Austin, Texas contingent - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows a group of people mingling around a banner that reads, "Austin, Texas supports the march. Friends of human rights". One person is signing the banner. Two men in cowboy hats hold flagpoles with what appears to be Texas state flags. They are participating in the National March on Washington for Lesbian and Gay Rights.